Processing Across Languages - Shelia Kennison (Frontiers Research Topics, 2018)
The Research Topic aims to highlight research on the processing of words, sentences and discourses across languages. Articles representing processing in a wide variety of human languages will be featured. Efforts will be made to have articles, representing as many language families as possible. The methodology used to investigate language processing is open. Manuscripts may report studies involving monolinguals or individuals knowing more than one language. Research addressing the extent to which all human languages are processed similarly are welcomed as are studies investigating the extent to which the different types of linguistic knowledge are stored differently in memory.